Synthesis and Properties of Waterborne Polyurethane Acrylates using Reactive Silicone. (24th July 2019) - Song, Sam Cha; Choi, Han Ho; Park, Kyung-Kyu; Lee, Seungjae; Lee, Won-Ki
Abstract: Since most of the coatings have been prepared by organic solvents, there are many regulations because of the environmental and health hazards caused by volatile organic compounds. As an alternative to organic solvent-based polyurethanes which are broadly used in coatings, waterborne polyurethane dispersions are receiving great attendance due to their harmless to humans and environment. In this study, water-dispersed UV-curable polyurethane acrylates were synthesized by varying content of reactive silicone which gives surface hydrophobic. The physical properties of the synthesized polyurethane acrylates were measured as a function of content of silicone. The molecular structure and physical properties of the synthesized water-dispersed UV-curable polyurethane acrylates were investigated by FT-IR and contact angle, surface energy, particle size, tensile strength, and elongation. The results showed that as the content of reactive silicone increased, the surface energy of the cured coating decreased due to hydrophobicity of silicone. The optimum physical properties were obtained by controlling content of reactive silicone.